Bifidobacterium breve intervention combined with environmental enrichment alleviates cognitive impairment by regulating the gut microbiota and microbial metabolites in Alzheimer’s disease mice - Zhu, Guangsu; Guo, Min; Zhao, Jianxin; Zhang, Hao; Wang, Gang; Chen, Wei (Frontiers in Immunology, 2022)
Alzheimer’s disease (AD) is characterized by behavioral and cognitive impairments and its increasing prevalence imposes a healthcare burden on society. To date, most intervention studies have only focused on a single AD-related factor and have yielded modest cognitive improvements. Here, we show that environmental enrichment (EE) training combined with Bifidobacterium breve CCFM1025 intervention significantly alleviated amyloid-β (Aβ)-induced cognitive impairment and inhibited neuroinflammation in mice. Moreover, we found that EE combined with B. breve CCFM1025 treatment restored AD-associated gut microbiota dysbiosis and reversed microbial metabolites changes. By integrating behavioral and neurological data with metabolomic profiles, we corroborated the microbiota–metabolite–brain interactions, with acetate and tryptophan metabolism as potential drivers. Taken together, our results provide a promising multidomain intervention to prevent cognitive decline and delay the progression of AD through a combination of dietary microbiome-based approaches and lifestyle interventions.